Decoding the universe [videorecording (DVD)] - McCabe, Daniel; McCabe, Daniel; Sanders, Jay O., 1953- (PBS, 2024)
Two-part Nova program exploring discoveries that have enhanced our understanding of the universe, looking at dark matter and dark energy, and the mysteries of the quantum universe, in which something on one side of the galaxy can affect something on the other side.